Competition, cost structure, and labour leverage: Evidence from the U.S. airline industry - Konstantin Wagner (Halle Institute for Economic Research (IWH), 2020)
I study the effect of increasing competition on financial performance through labour leverage. To capture competition, I exploit variation in product market contestability in the U.S. airline industry. First, I find that increasing competitive pressure leads to increasing labour leverage, proxied by labour share. This explains the decrease in operating profitability through labour rigidities. Second, by exploiting variation in human capital specificity, I show that contestability of product markets induces labour market contestability. Whereas affected firms might experience more stress through higher wages or loss of skilled human capital, more mobile employee groups benefit from competitions through higher labour shares.
urn:nbn:de:gbv:3:2-127919
Keywords: G39; J31; L93; 330; competition; labour leverage; labour share; threat of entry